Joint Distribution for the Risk Process with Premiums Depending on the Current Reserve - 何敬民 张炜 李曼曼 方鑫 (东华大学学报（英文版）, 2017)
With the ever-evolving of modern risk theory,more and more attention should be paid to the modification of the classical risk theory. In this paper a risk process with premiums dependent on the current reserve is considered. An explicit expression for the joint distribution of the time of ruin,the surplus immediately before ruin and the deficit at ruin is derived. Finally,some important actuarial diagnostics including the ultimate ruin probability is investigated.